Sistematik Literatur Review : Dampak Fatherless terhadap Kondisi Sosio-Emosional Anak - Jeni Fadhila; Kartika Aulia Rahmi; Muzhdhalifatul Azizah; Nurhasni Nurhasni; Amalia Kartika Yani; Maria Weni Gowasa; Mutiara Hendri (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
This research was conducted to describe the impact of fatherlessness on children's socio-emotional conditions. This topic was chosen because the presence of a father in a child's life has a very important role in shaping the child's socio-emotional aspects. However, the phenomenon of fatherlessness is increasing in society, whether due to divorce, problems in marriage, father's death, or fathers working outside the city. This research uses a systematic literature review to analyze data obtained from various sources. Based on the data findings, it can be seen that children who experience fatherlessness tend to have low self-confidence, have difficulty adapting to the social environment, and experience socio-emotional problems such as loneliness and loss. These impacts can be seen from various phases of development starting from early childhood, adolescence, even to early adulthood.